2015
DOI: 10.1007/s10620-015-3614-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Soluble Fas and Fas Ligand Levels Are Elevated in Children with Nonalcoholic Steatohepatitis

Abstract: Markers of the extrinsic pathway of hepatocyte apoptosis are elevated in children with NASH. sFasL and the NASH apoptosis score are potential novel biomarkers for NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The major features of these trials were summarised in Table 1 . After the whole presented workflow, 14 studies were admitted to our meta-analysis [ 9 – 11 , 20 30 ]. Input for NAFLD patients was carried only when a control group was not included in the study (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major features of these trials were summarised in Table 1 . After the whole presented workflow, 14 studies were admitted to our meta-analysis [ 9 – 11 , 20 30 ]. Input for NAFLD patients was carried only when a control group was not included in the study (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared SFL between NAFLD patients and controls, but they didn’t carry independent evidence on both NAFL and NASH [ 9 , 21 , 28 ]. Ten studies compared SFL between NAFL and NASH patients [ 10 , 11 , 20 , 22 , 23 , 25 – 27 , 29 , 30 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Fas, Fas ligand (FasL), and caspase 8 mRNA activation are important contributing factors to NAFLD[ 19 ]. Another study showed that children with NASH had significantly higher levels of soluble Fas and soluble FasL than those in the “not NASH” group[ 20 ]. Fas apoptosis inhibitory molecule (FAIM), a ubiquitously expressed antiapoptotic protein, functions as a mediator of Akt signaling[ 21 ].…”
Section: Apoptosis and The Activation Of Caspases In The Progression mentioning
confidence: 99%
“…Newly proposed markers: Serum potassium levels show an inverse relationship with the presence of aggressive disease (NASH and fibrosis) in children with NAFLD[ 57 ]. Markers of the extrinsic pathway of hepatocyte apoptosis [ e.g ., circulating soluble Fas and Fas ligand (sFasL) levels] that are elevated in children with NASH may be potential novel biomarkers[ 58 ]. Plasma cathepsin D (CatD) holds a high diagnostic value for distinguishing pediatric patients with hepatic inflammation from children with simple steatosis.…”
Section: Non-invasive Indirect Diagnosis Of Nafldmentioning
confidence: 99%